2014
DOI: 10.1089/lgbt.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

From Bias to Bisexual Health Disparities: Attitudes Toward Bisexual Men and Women in the United States

Abstract: PUROPSE A newly emergent literature suggest that bisexual men and women face profound health disparities in comparison to both heterosexual and homosexual individuals. Additionally, bisexual individuals often experience prejudice, stigma, and discrimination from both gay/lesbian and straight communities, termed “biphobia.” However, only limited research exists that empirically tests the extent and predictors of this double discrimination. The Bisexualities: Indiana Attitudes Survey (BIAS) was developed to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
206
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(222 citation statements)
references
References 33 publications
11
206
1
4
Order By: Relevance
“…The intersectionality framework may be especially useful for racial and sexual minority youth workers and clinicians in considering the experiences at the center of overlaping identities, i.e., Black, bisexual, and male (Fields et al, 2016). This developmental experience which prior work has documented as often occurring within homophobic, sexist and racist social contexts (Friedman et al, 2014; Jamil et al, 2009; Malebranche, 2008) may impact one’s ability to articulate and describe one’s sexual orientation. This may have important implications because romantic relationships may serve as a buffer against sexual orientation-based discrimination and micro-aggressions for sexual and racial minority youth during this time (Macapagal, Greene, Rivera, & Mustanski, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intersectionality framework may be especially useful for racial and sexual minority youth workers and clinicians in considering the experiences at the center of overlaping identities, i.e., Black, bisexual, and male (Fields et al, 2016). This developmental experience which prior work has documented as often occurring within homophobic, sexist and racist social contexts (Friedman et al, 2014; Jamil et al, 2009; Malebranche, 2008) may impact one’s ability to articulate and describe one’s sexual orientation. This may have important implications because romantic relationships may serve as a buffer against sexual orientation-based discrimination and micro-aggressions for sexual and racial minority youth during this time (Macapagal, Greene, Rivera, & Mustanski, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work exploring the sexual identity development experiences of sexual minority adolescents has failed to understand the sexual development of youth who may exist at the intersection of multiple marginalized identities, such as Black and bisexual (Dubé & Savin-Williams, 1999; Jamil, Harper,& Fernandez, 2009; Rosario, Schrimshaw,& Hunter, 2004,2008; Rosario, Schrimshaw, Hunter,& Braun, 2006; Toomey, Huynh, Jones, Lee, & Revels-Macalinao, 2017; Wade & Harper, 2015). Past work suggests that bisexual youth of color, including Black bisexual male adolescents (BBMA), may have significant and unmet sexual and reproductive as well as mental health needs during sexual development (Chun & Singh, 2010; Dodge et al, 2016; Friedman et al, 2014; Saewyc et al, 2009), which are unique and distinct from those adolescents who identify as gay, lesbian or heterosexual (Friedman et al, 2014; Mereish, Katz-Wise, & Woulfe, 2017). Understanding the context of sexual orientation development in BBMA may uncover key insights into opportunities for programmatic intervention in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in the Unites States has found that bisexual individuals face prejudice from both heterosexual and homosexual individuals, and that close to 15 percent do not trust that bisexuality is a legitimate sexual orientation (Friedman et al, 2014). The authors argue that the stigma faced by bisexual people may lead to them hiding their sexuality, in turn resulting in social isolation and negative mental health outcomes.…”
Section: Sexual Orientation Disclosure As a Mediator Of Mental Healthmentioning
confidence: 99%
“…The commentator describes this novel methodology as "forward-looking" because "it focuses on the knowledge that analyzing LGBT populations as a whole neglects many noteworthy features that affect only subgroups." As has been demonstrated by research, non-monosexual women may report worse mental health, may experience more lifetime adversity, and may face more stigma and discrimination than monosexual women (Friedman et al, 2011(Friedman et al, , 2014Kerr et al, 2013). Further, bisexual individuals may not feel part of the LGBT community (Herek et al, 2010).…”
mentioning
confidence: 97%
“…Future studies should continue to explore how mental health outcomes may vary by non-monosexual behavior versus by identifying as mostly heterosexual, bisexual, or mostly lesbian. For example, considering that "bisexual" appears to be a stigmatized label (Friedman et al, 2014;Zivony and Lobel, 2014), it is possible that those who behave bisexually without identifying as bisexual may be at lower risk of poor mental health compared to those who both behave bisexually and identify as bisexual. Schneeberger (2015) raises the very important question of whether stressful childhood experiences are relevant in nonmonosexual women.…”
mentioning
confidence: 99%